2016
DOI: 10.1590/1414-431x20165195
|View full text |Cite
|
Sign up to set email alerts
|

Blood levels of pro-inflammatory and anti-inflammatory cytokines during an oral glucose tolerance test in patients with symptoms suggesting reactive hypoglycemia

Abstract: We evaluated the impact of postprandial glycemia on blood levels of pro-inflammatory and anti-inflammatory cytokines during an oral glucose tolerance test in non-diabetic patients with symptoms suggesting reactive hypoglycemia. Eleven patients with clinical symptoms suggesting reactive hypoglycemia received an oral glucose solution (75 g) Blood was collected at 0 (baseline), 30, 60, 120 and 180 min after glucose ingestion and the plasma concentrations of interferon-α (IFN-α), interferon-γ (IFN-γ), interleukin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Therefore, it is possible that changes in TAC were missed either with acute changes occurring and waning between the exercise intervention and post exercise blood draw or occurring after the blood draw. Although the time course between cytokines and oxidative stress can be as short as 5 min [47], changes in both pro-and anti-inflammatory cytokines appear to change after 30 min postprandially, but not before [48]. Collection of blood samples at minute 30 in this current study may have been to early to capture differences in TAC.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, it is possible that changes in TAC were missed either with acute changes occurring and waning between the exercise intervention and post exercise blood draw or occurring after the blood draw. Although the time course between cytokines and oxidative stress can be as short as 5 min [47], changes in both pro-and anti-inflammatory cytokines appear to change after 30 min postprandially, but not before [48]. Collection of blood samples at minute 30 in this current study may have been to early to capture differences in TAC.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to these physiological changes, other mechanisms may play a role in the development of reactive hypoglycemia. Eik et al suggested that reactive hypoglycemia was associated with increased levels of anti--inflammatory and proinflammatory cytokines in the blood [21]. In another study, Berlin et al reported that patients with suspected postprandial hypoglycemia had increased beta--adrenergic sensitivity, and emotional distress [22].…”
Section: Discussionmentioning
confidence: 99%
“…MCP-5 is reported to be a murine homolog of human MCP-1, which is secreted by renal tubular epithelial cells and kidney mesangial cells during the process of inflammation and is differentially expressed in the kidneys [ 55 ]. Cytokines, as small proteins with multipotent biological features, including interleukins and interferons, show anti-inflammatory or proinflammatory properties [ 56 ]. Interleukins play an important role during the development of inflammation.…”
Section: Discussionmentioning
confidence: 99%